Role of Feed Processing on Gut Health and Function in Pigs and Poultry: Conundrum of Optimal Particle Size and Hydrothermal Regimens - Kiarie, Elijah G.; Mills, Alisha (Frontiers in Veterinary Science, 2019)
The aim is to give an overview of available literature data on the role of feed processing on gut health and function with specific focus on particle size and hydrothermal processing. In addition, influence of feed processing on efficacy of exogenous feed enzymes will be discussed. The current feed processing technologies are such that ingredient choices and diet form are refined to improve feed intake and nutrient utilization efficiency. Finer feed particle size enables optimal nutrient utilization and enhances animal performance due to increased surface area allowing better contact with digestive enzymes. Moreover, adequate diminution of feed ingredients is beneficial to feed manufacturing processes such as mixing and hydrothermal treatments including pelleting, extrusion, and expansion. However, emerging trends in consumer and regulatory demands for restriction or cessation of animal production practices such as use of antimicrobial growth promoters are challenging current approaches to feed processing. There is limit as to the fineness of the particle size, as very fine particles negatively affect gut health due to higher incidences of stomach ulceration in pigs and gizzard dysfunction in poultry. Coarse particle size increases stomach and hindgut acidification which may be beneficial in controlling proliferation of enteric pathogens such as salmonella and E. coli. Optimal particle size could be designed in the grinding process using roller or hammer mill. However, since most commercial pigs and poultry diets are subjected to hydrothermal processes, additional reduction of feed particle size is inevitable. The need to achieve high physical quality and to reduce potential levels of feed-borne pathogens such as Salmonella has led to the application of relatively high conditioning temperatures during conventional hydrothermal processes, a practice that does not favor high nutrient utilization and stability of heat sensitive feed additives such as feed enzymes. Therefore, with evolving pig and poultry production practices, the regimens for feed processing will no longer be appreciated only in terms of optimizing nutrients utilization, but also in terms of impact on feed hygienic status, efficacy of feed additives, animal health, and food safety.